Neocortical Microdissection at Columnar and Laminar Resolution for Molecular Interrogation. Issue 1 (4th October 2018) - Kole, Koen; Celikel, Tansu
Abstract: The heterogeneous organization of the mammalian neocortex poses a challenge for elucidating the molecular mechanisms underlying its physiological processes. Although high‐throughput molecular methods are increasingly deployed in neuroscience, their anatomical specificity is often lacking. In this unit, we introduce a targeted microdissection technique that enables extraction of high‐quality RNA and proteins at high anatomical resolution from acutely prepared brain slices. We exemplify its utility by isolating single cortical columns and laminae from the mouse primary somatosensory (barrel) cortex. Tissues can be isolated from living slices in minutes, and the extracted RNA and protein are of sufficient quantity and quality to be used for RNA sequencing and mass spectrometry. This technique will help to increase the anatomical specificity of molecular studies of the neocortex, and the brain in general, as it is applicable to any brain structure that can be identified using optical landmarks in living slices. © 2018 by John Wiley & Sons, Inc.